Kualitas Bakar Briket Bioarang Campuran Arang Kotoran Kambing dan Tempurung Buah Lontar (Saboak) dengan Level Perekat Berbeda: Burning Quality of Biocharcoal Briquettes Mixed of Goat Dung and Lontar Shell (Saboak) with Different Levels of Adhesive - Ervan Imanuel Taklal; Yakob Robert Noach; Twenfosel Ocsierly Dami Dato (Universitas Nusa Cendana, 2023)
The experiment goals was to determine burning quality of biocharcoal briquette mixed of goat dung and saboak shell with different levels of adhesive. Materials used consist of 8 kg of goat dung charcoal, 8 kg of saboak shell, 1.5 kg tapioca. The completely randomized design (CRD) consist of 4 treatments and 4 replications was applied. Those treatments were level of adhesive were P1: 6%, P2: 8%, P3: 10% and P4: 12%. The proporsion of both goad dung and saboak shell is 500 gram Variables observed were burning temperature, combustion rate, burning resistance, color and smoke and water boiling ability. Data were analyzed by analysis of variance (ANOVA). The statistical results showed that treatment have significant effect (P<0.05) on burning temperature but no significant (P>0.05) on combustion rate, burning resistance, color and smoke and boiling water ability. Burning temperature ranged 154.17 to 214.09oC; combustion rated ranged 2.14 to 2.44 g/minute; burning resistance ranged 164 to 188 minute; score of color 2.8 to 4 (tend to red until bluish) and score of smoke 3.85 to 4 (without smoke) and boiling water ability 19.5 to 27.75 minute. It can be concluded the increasing of adhesive levels decrease burning temperature, but no change on combustion rate, burning resistance, color and smoke and water boiling ability. The best burning quality of biocharcoal briquettes was founded at P1 that is 6% adhesive (P1). Penelitian bertujuan mengetahui kualitas bakar briket bioarang campuran arang kotoran kambing dan tempurung saboak dengan level perekat berbeda. Materi yang digunakan adalah kotoran kambing 8 kg, tempurung saboak 8 kg, tapioka 1,5 kg dan air. Metode yang digunakan yaitu Rancangan Acak Lengkap (RAL) dengan 4 perlakuan dan 4 ulangan. Perlakuan level perekat dari bahan bioarang yaitu P1: 6%, P2: 8%, P3: 10%, dan P4: 12%; proporsi kotoran kambing dan tempurung saboak masing-masing 500 gram. Variabel yang diteliti: temperatur bakar, laju pembakaran, ketahanan bakar, warna dan asap serta kemampuan mendidihkan air. Data dianalisis dengan analisis keragaman (ANOVA). Hasil analisis menunjukkan perlakuan berpengaruh nyata (P<0,05) terhadap temperatur bakar, berpengaruh tidak nyata (P>0,05) terhadap laju pembakaran, ketahanan bakar, warna dan asap serta kemampuan mendidihkan air. Temperatur bakar briket bioarang yang didapatkan berkisar 154,17-214,09oC; laju pembakaran 2,14-2,44g/menit; ketahanan bakar 164-188 menit; skor warna pembakaran 2,8-4 (cenderung merah - merah kebiruan) dan skor asap 3,85-4 (cenderung tidak ada asap - tidak ada asap) dan kemampuan mendidihkan air 19,5-27,75 menit. Disimpulkan bahwa naiknya level perekat menurunkan temperatur bakar tapi tidak menyebabkan perubahan laju pembakaran, ketahanan bakar, warna dan asap pembakaran serta kemampuan mendidihkan air. Kualitas bakar terbaik didapatkan pada P1 yaitu penggunaan level perekat 6%.